2016
DOI: 10.3389/fmicb.2015.01445
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Two ST 195 Carbapenem-Resistant Acinetobacter baumannii with Different Susceptibility to Polymyxin Revealed Underlying Resistance Mechanism

Abstract: Acinetobacter baumannii is a Gram-negative nosocomial pathogen of importance due to its uncanny ability to acquire resistance to most antimicrobials. These include carbapenems, which are the drugs of choice for treating A. baumannii infections, and polymyxins, the drugs of last resort. Whole genome sequencing was performed on two clinical carbapenem-resistant A. baumannii AC29 and AC30 strains which had an indistinguishable ApaI pulsotype but different susceptibilities to polymyxin. Both genomes consisted of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 79 publications
1
36
1
Order By: Relevance
“…Population structure of the isolates was quite variable with five different STs reported. ST 195 was previously reported in China and associated with OXA-23 β-lactamase in contrast with our study in which this ST was found in OXA-40 positive isolates [46][47] . In both studies ST195 isolates belonged to IC II.…”
Section: 5genotypingcontrasting
confidence: 99%
“…Population structure of the isolates was quite variable with five different STs reported. ST 195 was previously reported in China and associated with OXA-23 β-lactamase in contrast with our study in which this ST was found in OXA-40 positive isolates [46][47] . In both studies ST195 isolates belonged to IC II.…”
Section: 5genotypingcontrasting
confidence: 99%
“…Consistently, all the strains carrying armA (35/40, 87.5%) were resistant to gentamicin and tobramycin. The armA gene was located in the chromosome aboard on the widely disseminated Tn1548, and it was found downstream of a cluster of genes encoding proteins annotated as paraquat-inducible protein A and protein B, as previously described for ST195 strain AC29 (Lean et al, 2016).…”
Section: Antimicrobial Resistance Mechanisms and Phenotype Correlationmentioning
confidence: 90%
“…We used one representative A. baumannii clinical isolate to evaluate the phagemediated intercellular transfer of chromosomal ARGs. Although the presence of an identical NU60-I prophage (50 kb), carrying the capsid 1 gene found in the NU-60 genome, has not been admitted in any A. baumannii genome deposited in the database, the core capsid 1 protein gene involved in ARG transfer has been widely presented in A. baumannii strains isolated from geographically different areas, such as Japan (50), South Korea (51), China (52), Malaysia (53), and the United Kingdom (54). A similar phenomenon concerning the transfer of ARGs, using pelleted particles obtained through ultracentrifugation of culture supernatants, was identified when we used other A. baumannii clinical isolates (data not shown).…”
Section: Discussionmentioning
confidence: 99%